간호대학생들의 스마트폰 중독과 불확실성에 대한 인내력 부족이 정신건강에 미치는 영향: 회복탄력성의 매개효과 - 박정미; Jeong Mi Park (보건정보통계학회지, 2024)
Objectives: The purpose of this study was to confirm the mediating effect of resilience in the effects of smartphone addiction and intolerance of uncertainty on mental health of nursing students. Methods: The study subjects were 201 nursing students from Y University, with data collected from November 14 to 27, 2023, and the collected data were analyzed by SPSS 25.0. Results: The results indicated that smartphone addiction, intolerance of uncertainty, resilience, and mental health were all significantly correlated. Smartphone addiction and intolerance of uncertainty had a negative effects on mental health, and resilience had a partial mediating effect in this effect. Conclusions: This study suggested the importance of enhancing resilience as an intervention for improving the mental health of nursing students. In order to prevent mental illness and improve mental health of nursing students, it is suggested to develop and apply a specialized resilience promotion program for nursing students.